Manganese-Catalyzed ortho-Hydroalkylation of Aryl-Substituted N-Heteroaromatic Compounds with Maleimides - Shinde, Vikki N.; Bhawani, Bhawani; Nipate, Dhanajay S.; Sonam, Sonam; Meena, Neha; Rangan, Krishnan; Kumar, Dalip; Kumar, Anil (Synthesis, 2023)
A regioselective manganese-catalyzed ortho-hydroalkylation of aryl-substituted N-heteroaromatic compounds with a range of maleimides is described. The developed C–H bond functionalization protocol allowed the introduction of the succinimide motif at the ortho-position of the aryl ring of N-heteroaromatic compounds, such as 2-arylimidazo[1,2-a]pyridines, 2-arylindazoles, 2-phenylpyridine, 2-phenylpyrimidine, 2-phenylimidazo[1,2-a]pyrimidine, 2-phenylimidazo[2,1-b]thiazole, 2-phenylbenzo[d]imidazo[2,1-b]thiazole, 1-phenylindazole and 1-phenylpyrazole, to produce 3-(2-(N-heteroaryl)aryl)pyrrolidine-2,5-diones in good yields. The protocol exhibited broad substrate scope, good functional group tolerance and excellent regioselectivity under mild and additive-free reaction conditions.
Keywords: C–H functionalization; N-heteroaromatic compounds; hydroalkylation; maleimides; manganese